Polygenic and major‐locus contributions to sexual maturation timing in Atlantic salmon. Issue 18 (21st July 2021) - Debes, Paul V.; Piavchenko, Nikolai; Ruokolainen, Annukka; Ovaskainen, Outi; Moustakas‐Verho, Jacqueline E.; Parre, Noora; Aykanat, Tutku; Erkinaro, Jaakko; Primmer, Craig R.
Abstract: Sexual maturation timing is a life‐history trait central to the balance between mortality and reproduction. Maturation may be triggered when an underlying compound trait, called liability, exceeds a threshold. In many different species and especially fishes, this liability is approximated by growth and body condition. However, environmental vs. genetic contributions either directly or via growth and body condition to maturation timing remain unclear. Uncertainty exists also because the maturation process can reverse this causality and itself affect growth and body condition. In addition, disentangling the contributions of polygenic and major loci can be important. In many fishes, males mature before females, enabling the study of associations between male maturation and maturation‐unbiased female liability traits. Using 40 Atlantic salmon families, longitudinal common‐garden experimentation, and quantitative genetic analyses, we disentangled environmental from polygenic and major locus ( vgll3 ) effects on male maturation, and sex‐specific growth and condition. We detected polygenic heritabilities for maturation, growth, and body condition, and vgll3 effects on maturation and body condition but not on growth. Longitudinal patterns for sex‐specific phenotypic liability, and for genetic variances and correlations between sexes suggested that early growth and condition indeed positively affected maturation initiation. However, towards spawning time, causality appeared reversed for males whereby maturation affected growth negatively and condition positively via both the environmental and genetic effects. Altogether, the results indicate that growth and condition are useful traits to study liability for maturation initiation, but only until maturation alters their expression, and that vgll3 contributes to maturation initiation via condition.